AUDIT GOING CONCERN OPINION: THE EFFECT OF COMPANY GROWTH, AUDIT TENURE AND AUDIT DELAY AS MODERATING VARIABLE - Amalia Islami; Mukhtaruddin Mukhtaruddin; Kencana Dewi; Asfeni Nurullah (AKUNTABILITAS, 2022)
Going concern (GC) audit opinion is an opinion given when the auditor has doubts about the going concern of a company. The purpose of thisresearch is to find out the effect of company growth (CG) and audittenure(AT)withauditdelay(AD)asmoderating to GC audit opinion. This research used secondary data in the form of a companyannual report. Population of this research is companies in property,realestate,andconstructionbuilding sectors inIndonesia Stock Exchange during three years.The sample selection used purposive sampling and the total samples are 62 samples with 186 observation data.This study use dlogistic regression analysis. The results show that CG, AT, and AD which moderate AT do not affect GC audit opinion, but AD which moderates CG effects GC audit opinion. Limitation of this research is small sample size, so it is recommended in the futureresearch to add more samplesin order to show maximum results.